2013
DOI: 10.1128/jvi.03111-12
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Viral and Cellular Gene Expression by Kaposi's Sarcoma-Associated Herpesvirus Polyadenylated Nuclear RNA

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the cause of Kaposi's sarcoma and body cavity lymphoma. In cell culture, KSHV results in a latent infection, and lytic reactivation is usually induced with the expression of K-Rta or by treatment with phorbol 12-myristate 13-acetate (TPA) and/or n-butyrate. Lytic infection is marked by the activation of the entire viral genomic transcription cascade and the production of infectious virus. KSHV-infected cells express a highly abundant, long, noncoding transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
197
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(199 citation statements)
references
References 36 publications
(39 reference statements)
1
197
1
Order By: Relevance
“…PAN RNA knockdown during reactivation was accompanied by higher levels of episome-associated LANA and reduced viral gene expression; this is consistent with a repressive role of LANA in lytic gene expression in general (23). Of note, we also noticed that a few viral gene expression patterns did not follow the same trend in our PCR array analyses, which is consistent with a previous report (10), indicating that PAN RNA may have other functions. Importantly, similar to viral gene regulation, Affymetrix human gene expression arrays showed that PAN RNA also regulates cellular gene expression targeted by LANA (data not shown).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…PAN RNA knockdown during reactivation was accompanied by higher levels of episome-associated LANA and reduced viral gene expression; this is consistent with a repressive role of LANA in lytic gene expression in general (23). Of note, we also noticed that a few viral gene expression patterns did not follow the same trend in our PCR array analyses, which is consistent with a previous report (10), indicating that PAN RNA may have other functions. Importantly, similar to viral gene regulation, Affymetrix human gene expression arrays showed that PAN RNA also regulates cellular gene expression targeted by LANA (data not shown).…”
supporting
confidence: 81%
“…PAN RNA binds the transcription factor IRF4 (8), lysine demethylases UTX and JMJD3, and the lysine methyltransferase MLL2 (9), in support of the notion that, similar to cellular lncRNAs, PAN RNA interacts with transcriptional regulators and chromatin modifiers to modulate viral gene expression. Moreover, recent mapping studies have found widespread PAN RNA interaction sites on the KSHV episome as well as the host genome, and PAN RNA expression is required for optimal expression of the entire KSHV lytic gene expression program (10).…”
mentioning
confidence: 99%
“…Although not directly assessed in our study, we speculate that one function of PAN may be to trap cellular RNAPII on the KSHV genome through DNA-RNA or RNA-protein interactions. PAN has been reported to interact with several viral and cellular proteins [24][25][26][27] , and its communication network is probably incompletely defined. In addition, it is also possible that the process of transcription itself may contribute to PAN function through an enhancer-RNA-like activity to facilitate reactivation [28,29] .…”
Section: Research Highlightmentioning
confidence: 99%
“…On the promoter of the transitional viral transactivator RTA/ORF50, PAN RNA interacts with demethylases JMJD3 and UTX. The ChIRP technique was extended in a global high-throughput manner and revealed ubiquitous PAN RNA binding along the entire viral genome (Rossetto et al 2013). Confirmation using a related technique, such as CHART, might clarify the specificity of PAN RNA's binding to viral chromatin.…”
Section: Abundant Long Ncrnas (Lncrnas) That Span the Herpesvirusesmentioning
confidence: 99%